Influence of fire on soil and vegetation properties in two contrasting forest sites in Central México - Capulin-Grande,Juan (Pontificia Universidad Católica de Chile. Facultad de Agronomía e Ingeniería Forestal, 2018)
Abstract Fire produces changes in vegetation, soil, fauna, and water quality, and it can even modify atmospheric chemical composition. Changes in soil fertility, microorganisms and vegetation were evaluated after a fire in two municipalities in the State of Hidalgo, Mexico. Inside and outside the burned area, four 100 m2 plots were established. In each of the eight plots, soil samples were collected at two depths (0-5 and 5-20 cm) in the following areas: non-burned area (NBA); 15 days after fire (15DAF); and 12 and 24 months after the fire (MAF). Vegetation quantification was carried out at 30, 180 and 540 DAF. The results at 15DAF showed an increase of alkaline and metallic elements as well as pH in the surface layer, and this trend remained the same to 12MAF. There was greater Fe, Mn and Zn content in Zacualtipán and greater K, Ca, Mg and P in Singuilucan. At 24MAF, due to the nutrient requirements of the herbaceous and scrub growth, this effect was reverted. The fire reduced the organic matter (OM) and total nitrogen (TN) contents, without any recovery during the evaluated period. Bacteria showed greater mortality because of the fire: 76% and 50% at the Zacualtipán and Singuilucan sites, respectively. The canopy opening promoted a 50% increase of species in Zacualtipán. In conclusion, the fire temporarily increased soil fertility and the presence of herbaceous vegetation, but it reduced the bacteria and fungi populations.